2021
DOI: 10.3390/s21144838
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Feature Extraction Methods for Physiological Signals for Heat-Based Pain Recognition

Abstract: While even the most common definition of pain is under debate, pain assessment has remained the same for decades. But the paramount importance of precise pain management for successful healthcare has encouraged initiatives to improve the way pain is assessed. Recent approaches have proposed automatic pain evaluation systems using machine learning models trained with data coming from behavioural or physiological sensors. Although yielding promising results, machine learning studies for sensor-based pain recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…Overall the results of this study are similar to what was reported in related works [ 2 , 3 , 4 , 14 , 15 , 18 , 19 , 20 , 21 ]. Nonetheless, this investigation goes further than previous literature, since it uses a higher number of physiological data, and, thus, a deep analysis of the effects of pain in the body.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall the results of this study are similar to what was reported in related works [ 2 , 3 , 4 , 14 , 15 , 18 , 19 , 20 , 21 ]. Nonetheless, this investigation goes further than previous literature, since it uses a higher number of physiological data, and, thus, a deep analysis of the effects of pain in the body.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the results for the EMG features validate the previous research in the area [ 15 , 19 ]: firstly, the RMSA, where both muscles showed a well-marked of value boxplots for the CPT epoch, thus corroborating the premise of reaction on the ANS due to the presence of pain. The statistical analysis shows that the Baseline presents significant differences with all the remaining epochs, indicating that, during the Rest, the muscle did not recover to the original state, whereas the triceps show differences between the baseline and the remaining epochs, except for the Rest period, indicating that it was able to recover.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…During each repetitive paradigm, the respiBAN Professional (Plux; a chest‐worn device that registers various physiological modalities at a sampling rate of 1000 Hz) was used to collect physiological data derived from the OpenSignals software (PLUX Wireless Biosignals S.A). EDA was measured using two Ag/AgCl hydrogel electrodes (Covidien/Kendall) at the medial phalanx of index and middle fingers of the non‐dominant arm (Gouverneur et al, 2021; Posada‐Quintero & Chon, 2020). Participants were asked to wash their hands with ordinary soap immediately before attaching the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Support vector machine (SVM) [ 59 ], random forest (RF) [ 60 ], k-nearest neighbors (KNN) [ 61 ], decision tree [ 62 ], etc., are among the most popular classifiers used in the past literature. In this paper, a soft-margin SVM (known as a C-SVM) with a radial basis function (RBF) kernel and a RF classifier are the two chosen classifiers due to their high performance and ability to overcome overfitting in the case of high dimensional data [ 14 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%